Propuesta de mejoramiento del sistema existente de alcantarillado sanitario en el sector Samanes 6 Guayaquil - García Peñaherrera, Keyla Nayely (2024)
Sector 6 is located in the city of Guayaquil. According to the research carried out through surveys, field research and trials, there is no doubt about the need to implement proposals and possible improvements to the sewerage system. The scope of this descriptive research, based on the hypothesis proposed, relates the variables. Therefore, once the information has been collected, the concepts are systematically categorized and the results are deduced. Thus, the results were obtained in terms of the sulphide and H2S tests in which the implementation of two innovative proposals of chemical compounds was proposed, which is ferric chloride and anti-odor filters with activated carbon to provide possible solutions in wastewater for this sector as they require it.